Mendulang Hikmah dibalik Kisah Akhlak Mulia Seorang Anak kepada Orangtuanya : Kisah Juraid Dalam Q.S Al-Isra Ayat 23 - Sarah Dalila Fitri; Rodia Rotani Rianda; Bella Anggraini; Lara Dwi Alma; Wismanto (STIKes Ibnu Sina Ajibarang, 2024)
As good Muslims, we must always obey our parents, do what our parents tell us to do, and never disobey. However, nowadays, many of us seem to forget our obligations towards our parents as good Muslims, namely having good morals. perfect towards parents. The presence of parents truly provides peace, love and affection in the hearts of all intelligent people. The aim of this research is to reveal the concept of the moral goals of children towards their parents. The method used in this research is a qualitative method with a library research approach by using books, magazines and articles related to this research theme as the main data source. The results of this research show that children's morals towards parents contained in Surah Al-Isra verse 23 are about the meaning of morals and both parents, so it can be said that for both parents, morals are the human soul which gives birth to good deeds because of habit without thinking and reflect, so that it becomes a strong personality in the human soul who always does. both to the people who cared for him since he was in the womb or after he grew up. Doing good to both parents is better known as Birrul Walidain, which means fulfilling the rights and obligations of parents towards both of them. Keep obeying both, do things that make you happy and don't harm them.